Habit and Exemplary Applied to Optimize the Intelligence of Muhammadiyah Elementary School Students in Surabaya City - Martati, Badruli; Yunianti, Sofi (Middle European Scientific Bulletin, 2021)
Educating the life of the nation is the goal of the Republic of Indonesia. The importance of an intelligent nation has been understood by K.H. A. Dahlan since 1928. To realize a smart nation is done through education. The case of bullying that occurs in elementary school children is an example of educational failure. Is there a wrong value received by the child? The purpose of the study was to determine the spiritual intelligence of Muhammadiyah Elementary School students in Mulyorejo District, Surabaya City. A descriptive research, with field studies directly on the object of research in actual conditions, namely SD Muhammadiyah Surabaya, collecting data with questionnaires.